Changing of the characteristics of the labor potential in the transition to the technogenic society - O. A. Tettsoeva (Управление)
The issues of changing the characteristics of labor potential in the transition to the technogenic society in the postindustrial community, which the processes of further urbanization and development of mega-cities are typical for, – have been examined. The technogenic society has been considered as the community, the basis of which is characterized by reducing dependence of a person on social groups, amplification of personality in creative work, changing of motivation pattern, high pace of social changes, alteration of interpersonal communication models. The movement of quantitative characteristics of labor potential is due to decreasing birth rates, the increasing share of older age groups, the downward changing of migration scale. Trends in the qualitative characteristics are pre-determined by the possibility of continuous learning and self-education. This in turn leads to changing of the situation in the labor market, where low-skilled workers are becoming non-competitive. High qualification fundamentally change an employee’s motivation: the significance of material incentives decreases, external motivation changes for the internal one, the meaningfulness of work, the independence of work performance, the responsibility for decisions taken, become an issue of the highest priority.The transition to the new culture of the technogenic society requires alteration of both professional and personal communications. The communication environment moves increasingly into the virtual world. However, a need is noted to lay emphasis upon the risks of the technogenic society, that relate to the increased scale of a person’s presence in the virtual world and to manage such risks. The risks of the technogenic society are connected with a person’s dependence on cyberspace, which has a negative impact on his or her mental health, and permanent using of electronic devices pre-determines risks of deteriorating his or her physical health. The digital transformation of the society requires the special attention to the safety of presence in cyberspace not only from the point of view of anonymizing of the personalized content, that identifies a particular person, but also taking into account the geolocation of his or her physical presence in the geographical coordinates of the real space. With the virtualization of all aspects of a person’s life, there are the increased risks of changing attitude towards the family values, forming the fundamental basis of the society’s functioning. The technogenic society contributes the risk of conscious single life, rejection family values. This risks will be catastrophic for the existence of humanity.